2014
DOI: 10.1136/bjsports-2013-092904
|View full text |Cite
|
Sign up to set email alerts
|

A modified prebind engagement process reduces biomechanical loading on front row players during scrummaging: a cross-sectional study of 11 elite teams

Abstract: Using a scrum engagement process which involves binding with the opposition prior to the engagement reduces the stresses acting on players and therefore may represent a possible improvement for players' safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(99 citation statements)
references
References 31 publications
(18 reference statements)
5
94
0
Order By: Relevance
“…While many studies have examined the components of scrum force [2][3][4][15][16][17] the movement of the CoP elicited during scrummaging in a forward direction, a measurement of the vector through which force is applied, has not yet been studied. By identifying group and individual scrumming CoPs a player or team could work to maximise summation of forces from different elements of the scrum or alter CoP position to attack the opponent's weaker area.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have examined the components of scrum force [2][3][4][15][16][17] the movement of the CoP elicited during scrummaging in a forward direction, a measurement of the vector through which force is applied, has not yet been studied. By identifying group and individual scrumming CoPs a player or team could work to maximise summation of forces from different elements of the scrum or alter CoP position to attack the opponent's weaker area.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative research on the rugby scrum has been occasional14 22–24 and has demonstrated that high forces can be generated, particularly during the engagement phase 14. Recent research has increased the scale and scope of the biomechanical investigation of the scrum,15 25 and has moved the investigation into live contested scrummaging to improve the ecological validity of the data 26…”
Section: Introductionmentioning
confidence: 99%
“…Notably, after the scrum was identified as having a high propensity for injury,1 engagement strategies were changed on the basis of research studies, resulting in reduced biomechanical loading on front row players by ∼20% 2. This research ultimately led to a worldwide law amendment across all levels of the game.…”
mentioning
confidence: 99%